Improving the Predictability of Two Types of ENSO by the Characteristics of Extratropical Precursors. Issue 3 (8th February 2022) - Tseng, Yu‐heng; Huang, Jo‐Hsu; Chen, Han‐Ching
Abstract: The Central Pacific (CP) and Eastern Pacific (EP) types of El Niño‐Southern Oscillation events are distinctly different in terms of their forming locations and mechanisms. Using an updated physical‐base statistical forecast model, the forecast of CP indices has overall higher skills than that of EP indices due to the higher persistent forecast skill. At lead time beyond 6‐month, the predictability of CP indices can be greatly enhanced by including the extratropical precursor from the North Pacific, confirming the ocean‐atmosphere interaction associated with North Pacific Oscillation (NPO)/Victoria Mode (VM) evolution. The predictability of EP indices can be moderately enhanced by including the extratropical precursor from the south, resulting from the charging of the equatorial Pacific. We also find that the predictability of CP indices does not significantly decrease after 2000 while the predictability of EP indices drops dramatically, suggesting the strengthening impacts of NPO/VM on the CP‐ENSO in the recent two decades. Plain Language Summary: The predictability of different types of El Niño‐Southern Oscillation (ENSO) events can be significantly enhanced by including extratropical signals using a physical‐base statistical forecast model. At a lead time longer than 6‐month, the predictability of Central Pacific ENSO can be greatly enhanced by including the extratropical signal from the North Pacific, confirming a well‐known ocean‐atmosphere interaction process proposed earlier. The predictability of Eastern Pacific ENSO can be moderately enhanced by including the extratropical precursor from the south, resulting from the charging of the equatorial Pacific. We also find that the predictability of CP indices does not significantly decrease after 2000 while the predictability of EP indices drops dramatically, suggesting the enhanced north hemispheric impacts in the recent two decades. Key Points: Both predictabilities of Central Pacific (CP)/Eastern Pacific (EP) El Niño‐Southern Oscillation (ENSO) can be greatly enhanced by including the Pacific extratropical precursors The distinct roles of North and South Pacific precursors on the CP and EP ENSO, respectively, are clarified The stable/decreased predictability of CP/EP indices after 2000 confirms the recent enhanced NPO‐relevant impacts